The nearly 100% filling of PEDOT in TiO2 nanotube array by a simple electropolymerization method - Yang, Xiuchun; Chi, Lina; Chen, Chao; Cui, Xiaolin; Wang, Qingyao (Physica. E, Low-dimensional systems & nanostructures, 2015)
A nearly 100% filling of PEDOT in TiO2 nanotube array (NTA) was successfully prepared by a simple electropolymerization method at a constant potential of 1.8V, which was demonstrated by field emission scanning electron microscopy (FESEM). UV–vis diffusion reflection spectroscopy (DRS) revealed that the filling of PEDOT in TiO2 NTA can dramatically improve the visible-light and near-infra-red absorption property of the TiO2 NTA, which is especially useful for the application of solar cells. Cyclic voltammetry experiments indicate that the PEDOT–TiO2 NTA hybrid material is electrochemically more active than the TiO2 NTA and has excellent redox reversibility. The PEDOT–TiO2 NTA hybrid material has been successfully prepared by a simple electropolymerization method, which exhibits an excellent light absorption property, electrochemical activity and redox reversibility. [Display omitted] •A nearly 100% filling of PEDOT in TiO2 NTA was successfully prepared.•PEDOT can dramatically improve the visible-light and near-infra-red absorption.•The hybrid material has excellent redox reversibility and electroactivity.